Pediatric Pulmonology year in review 2015: Part 1. Issue 7 (28th April 2016) - Auten, Richard; Schwarze, Jurgen; Ren, Clement; Davis, Stephanie; Noah, Terry L.
Summary: Our journal covers a broad range of research and scholarly topics related to children's respiratory disorders. For updated perspectives on the rapidly expanding knowledge in our field, we will summarize the past year's publications in our major topic areas, as well as selected publications in these areas from the core clinical journal literature outside our own pages. The current review covers articles on neonatal lung disease, pulmonary physiology, and respiratory infection.Pediatr Pulmonol. 2016;51:733–739 . © 2016 Wiley Periodicals, Inc.